Improving quranic exegesis learning through podcast learning media for high schools - Asda Amatullah; Ahmad Nurrohim; Naadiyah Syifaul Ummah; Annisa Nur Izzati; Fatimah Salma Az-Zahra; Jessenia Hayfa Anshara; Qomariah Nur Mujahidah; Ahmad Mulalic (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2024)
The purpose of this research is threefold: first, to create a high-quality podcast as a learning tool for students; second, to validate podcasts with experts in their fields; and third, to assess how well the podcast works with students in grade twelve at Madrasah Aliyah PPMI Assalaam. Students from experimental class XII (n=35) participated in this study. The Classroom Action Study method, created by Kemmis and Mc Taggart, was used in this research and development. The procedure is carried out in the following order: (1) preparation, (2) implementation, (3) monitoring, and (4) analysis. Observation, interviews, testing, and documentation are the methods used to collect information for efficacy tests. Students can be motivated, their attention captured, their knowledge deepened, their learning outcomes improved, and their learning goals met with the help of high-quality podcast material. Student performance in the pre-cycle, the results of the presentation of the first cycle and the next stage of activities from the second cycle are indications of program efficacy. The findings of the study suggest that high school students can benefit from using audio podcasts as a learning tool. The feasibility test of the voice podcast learning media, which includes master validation in operational field experiments, yielded "Good" results. The use of audio podcasts as a teaching tool significantly improves students' presentation completion scores compared to the use of traditional teaching methods.